2015
DOI: 10.1038/srep11378
|View full text |Cite
|
Sign up to set email alerts
|

Growth from behind: Intercalation-growth of two-dimensional FeO moiré structure underneath of metal-supported graphene

Abstract: Growth of graphene by chemical vapor deposition on metal supports has become a promising approach for the large-scale synthesis of high quality graphene. Decoupling of the graphene from the metal has been achieved by either mechanical transfer or intercalation of elements/molecules in between the metal and graphene. Here we show that metal stabilized two-dimensional (2D)-oxide monolayers can be grown in between graphene and the metal substrate thus forming 2D-heterostructures that enable tuning of the material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 70 publications
5
37
0
4
Order By: Relevance
“…Imaging on a separate region on the monoatomic graphene lattice, we also observed point defects exhibiting a two-fold symmetry ( Fig. 3f ) as previously observed on monolayer graphene imaged in a UHV-based STM using non-functionalized metal tips 42 . The occurrence of corrugations and point defects, appearing as protrusions on the atomic lattice, is dependent not only on the synthesis mechanism but relates strongly with the registry of these materials to the underlying surface and its roughness 43 .…”
Section: Resultssupporting
confidence: 82%
“…Imaging on a separate region on the monoatomic graphene lattice, we also observed point defects exhibiting a two-fold symmetry ( Fig. 3f ) as previously observed on monolayer graphene imaged in a UHV-based STM using non-functionalized metal tips 42 . The occurrence of corrugations and point defects, appearing as protrusions on the atomic lattice, is dependent not only on the synthesis mechanism but relates strongly with the registry of these materials to the underlying surface and its roughness 43 .…”
Section: Resultssupporting
confidence: 82%
“…It has been previously demonstrated that the thermal treatment at a temperature of 600-700 K results in complete Fe diffusion in between single layer Gr and Pt(111) substrate and morphology transition from small nanoparticles to atomically flat Fe layer. Furthermore, the intercalated iron was found to be remarkably protected from the interaction with the environment under ambient conditions [12,23]. Our results show that the situation is different in the case of h-BNG layer.…”
Section: Discussionmentioning
confidence: 73%
“…Among these surfaces, those of FeO have an additional interest to design exchange bias nanocomposites 6,7 . Particularly, the FeO(111) termination is a good candidate to achieve large perpendicular magnetic anisotropy 8 and has already been used as support of hexagonal two-dimensional materials like graphene 9 .…”
Section: Introductionmentioning
confidence: 99%